2016
DOI: 10.1002/mds.26809
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characteristics of transactive response DNA binding protein 43 kDa pathology in progressive supranuclear palsy

Abstract: Introduction This study aimed to determine the frequency of transactive response DNA binding protein 43 kDa (TDP-43) pathology in PSP, the clinical features of patients with this pathology, and genetic risk factors for it.. Methods Hippocampal sections were screened with immunohistochemistry for TDP-43 in 945 PSP cases. A subset of 261 cases that were negative in hippocampus was screened in the amygdala. The density and disruption of this pathology, as well as regional tau burden, and clinical and genetic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 45 publications
2
51
1
Order By: Relevance
“…The frequency of TDP-43 pathology in CBD (45%) was much higher than that of PSP from literature (0% to 26%) [29,63,60,52], although the screening method was different among the studies. To compare the frequency of TDP-43 pathology between CBD and PSP with the same method, we screened 40 consecutive PSP cases using sections of the midbrain, pons, basal forebrain including the amygdala, and subthalamic nucleus.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The frequency of TDP-43 pathology in CBD (45%) was much higher than that of PSP from literature (0% to 26%) [29,63,60,52], although the screening method was different among the studies. To compare the frequency of TDP-43 pathology between CBD and PSP with the same method, we screened 40 consecutive PSP cases using sections of the midbrain, pons, basal forebrain including the amygdala, and subthalamic nucleus.…”
Section: Resultsmentioning
confidence: 59%
“…Several studies showed that TDP-43 pathology was frequent (55–60%) in the limbic structures in AGD [13,59]. AGD coexisted more frequently in TDP-43 positive PSP compared with TDP-43 negative PSP [29]. In addition, many cases of multiple system atrophy with extensive TDP-43 pathology had concurrent AGD [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arnold et al demonstrated argyrophilic grains, but not age or Alzheimer's-type pathology was correlated with frequency of TDP-43 pathology in cognitively normal elderly individuals [30]. Similarly, the previous study showed that concurrent AGD was a risk factor for TDP-43 pathology in PSP [27]. Taken together, AGD may be associated with TDP-43 pathology in MSA; however, it is still unknown whether AGD can cause widespread TDP-43 pathology beyond limbic structures affected by AGD.…”
Section: Discussionmentioning
confidence: 98%
“…who agreed on the presence of TDP-43 immunoreactivity, defined as NCI, GCI, DNs, fine neurites, neuronal intranuclear inclusions, spheroids, or perivascular inclusions in any region. The severity of TDP-43 pathology was graded semi-quantitatively on a four-point scale (0 = absent, 1 = mild, 2 = moderate, 3 = severe) [27]. …”
Section: Methodsmentioning
confidence: 99%